Ukraine : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the details of the IMF's projections and estimates on Ukraine's basic data; gross domestic product; utilization of gross domestic product during 1997-2000 (June); gross investment; output of major agricultural products; population, labor force, and employment; central and local government budgets; summary balance of payments, 1996-99; consolidated budget revenues and expenditures, 1996-June 2000; monetary survey; interest rates, 1997-99; services account, 1995-99; interest rates; accounts of the national bank of Ukraine; summary indicators of money and credit during 1997-99; tax summary; and so on.